Neoadjuvant serplulimab and SOX chemotherapy for locally advanced gastric cancer: pathological responses and systemic immune signatures from a phase II trial - Zhan, Hongjie; Liu, Liang; Cai, Mingzhi; Sun, Weilin (Frontiers in Immunology, 2026)
BackgroundNeoadjuvant immunotherapy combined with chemotherapy is an emerging strategy for improving outcomes in patients with locally advanced gastric cancer (LAGC). However, clinical evidence regarding the efficacy of serplulimab plus SOX chemotherapy and its immunologic correlates remains limited.MethodsIn this prospective, single-center, phase II trial, patients with cT3-4N+M0 resectable gastric or gastroesophageal junction adenocarcinoma received three cycles of serplulimab combined with SOX chemotherapy, followed by D2 gastrectomy and adjuvant therapy. The primary endpoints were pathological complete response (pCR) and major pathological response (MPR). Circulating immune markers, including cytokines (e.g., IL-1β, TNF-α) and T-cell subsets (e.g., CD4+/Treg ratio), were profiled longitudinally to evaluate immune remodeling during neoadjuvant therapy. The exploratory role of perioperative parenteral nutrition (PN) was also assessed.ResultsAmong the 33 enrolled patients, all underwent surgery and achieved R0 resection. The pCR and MPR rates were 21.21% and 36.36%, respectively. The 12-month event-free survival (EFS) rate was 82.20% (68.99-97.94). Patients achieving MPR exhibited elevated preoperative IL-1β levels, a lower CD4+/Treg ratio, and a higher Treg/CD8+ ratio, suggesting that systemic immune activation may predict better pathological response. While PN transiently preserved lymphocytes and reduced inflammation preoperatively, it showed no sustained postoperative immune effect.ConclusionNeoadjuvant serplulimab plus SOX chemotherapy demonstrates promising efficacy in LAGC, with immunologic remodeling potentially serving as a predictor of treatment response. The identification of non-invasive, blood-based immune biomarkers may help guide future patient selection and therapeutic optimization. The ongoing phase III trial (NCT04139135) will validate the efficacy of this perioperative immunochemotherapy strategy in LAGC.